Persepsi Masyarakat tentang Citra Pemerintah Kota Medan Melalui Akun Media Sosial Instagram @humas_pemkomedan - Effendi, Muhammad Wahyu; Hendra, Yan; Matondang, Armansyah (Universitas Medan Area, 2019)
This research is based on the social media account of Instagram @humas_pemkomedan which contains the image of Medan City Government. The purpose of this study to determine the public perception about the image of Medan City Government through social media accounts Instagram. Theories used in this study include the theoretical description of communication, perception, society, image, social media, Instagram. The research method used is qualitative descriptive method. Selection of informants here is the people of Medan City who follow social media accounts Instagram @humas_pemkomedan and informants in this study following the principle of saturation where if the data needed is still less will be done addition of informants to get new information until the data obtained reach saturation point that if from the source is the same, then the data collection through the interview is stopped. Data collection?? techniques? were? conducted?? by? semi-structured interviews to all informants, and the results of this study showed that where the perception of the image is described into the first two aspects through Instagram profile and the second is the content of Instagram @humas_pemkomedan consisting of 6 categories of uploads are as follows: The activities of Medan city administration, news reports on work, information and appeal, congratulations, videos, figures, then Public Perceptions About Government Image Medan City Through Social Media Account Instagram is tend to be positive.